Republic of India--Livelihoods in Intermediate Towns : Social Dynamics of Non-farm Economy - World Bank (Washington, DC, 2015)
This report is based on a field study of two large settlements, Satghara (a census town) and Bhagwatipur (a rural cluster with 10,000 plus population) in the Madhubani district of Bihar. The study explores the social dynamics of the rural non-farm economy by empirically mapping non-farm occupations in both the settlements. It examines the dynamics of caste, community, and gender within the social organization of the non-farm economy in terms of their economic and social hierarchies and the differential incomes and status they provide. The study also looks at the relationship of the local non-farm economy with patterns of outmigration. It further attempts to understand the manner in which the changes in the regional structures of power and domination have influenced the local economic processes and are being influenced by them with a specific focus on the non-farm economy in the two setting. The study also attempts an assessment of the possible development and urbanizing effects of the rather rapid growth of nonfarm economy in rural Madhubani.